STRATEGI PENINGKATAN KUALITAS JASA WISATA PENDAKIAN GUNUNG BATUR - Arta Widana, I Ketut (WIDYA DUTA, 2012)
The gap between tourists´ expectation and perceived service has made some service failure on the Mount Batur trekking attraction. Based on that reason, research on the strategy to improve quality service is very interesting to conduct. Three research problems are proposed: (1) How is the quality standards of the Mount Batur trekking attraction?, (2) How is the tourists´ satisfaction against the service perceived?, (3) What strategy is built for service improvement?. This research is to find the quality standards built, to know the satisfaction level of the tourists, and the strategy built by service provider and other stakeholders to improve service quality. The combination of qualitative and quantitative approaches known as mixed-method is used to analyze the problems. The result found that there are 30 indicators composing the quality standards. In general, based on ServQual analysis of 150 questionnaires shared, the perceived performance score was over than the expected service meaning that it produced customers´ satisfaction. Service failure was found specifically in 7 out of 30 indicators. Roles of all key actors related to the sustainability of the attraction and the physical environment of Mount Batur need to be improved. Some strategies were proposed including environmental strategy, cultural strategy, community involvement strategy, and integrated marketing communication strategy. Key words: Strategy, Service quality, Mount Batur trekking attraction.